First record of Pontinus kuhlii in Maltese waters. (14th January 2014) - Castriota, Luca; Deidun, Alan
Abstract : The presence of the offshore rockfish, Pontinus kuhlii (Scorpaeniformes, Scorpaenidae), is reported for the first time in Maltese waters (Strait of Sicily). One specimen was caught offshore Gozo (Maltese archipelago) in October 2013 by bottom longline. The eastward range expansion within the Mediterranean of this Atlantic species is discussed.